Hard coat resin composition and hard coat film

JP7630263B2Active Publication Date: 2025-02-17AICA KOGYO CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020199259
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-11
Filing Date
2020-12-01
Publication Date
2025-02-17
Estimated Expiration
2040-12-01

Smart Images

  • Figure 0007630263000001
    Figure 0007630263000001
  • Figure 0007630263000002
    Figure 0007630263000002
  • Figure 0007630263000003
    Figure 0007630263000003
Patent Text Reader

Abstract

To provide: a photocurable resin composition, which has excellent optical characteristics as well as abrasion resistance, and which has a very small rate of change in a water contact angle even when abraded with an eraser; and a hard coat film having a cured layer of the resin.SOLUTION: A hard coat resin composition comprises: a binder containing a polythiophene-based compound; a fluorine-based compound having a reactive functional group; and a photoinitiator. The binder contains 6 or more functional (meth)acrylate, a ratio of the fluorine-based compound relative to 100 pts.wt. of photocurable components is 0.3 to 12.0 pts.wt., and a water contact angle of a cured film is 100° or more and, when a rubber eraser is reciprocated under a load of 1 Kg for 1000 times, a rate of reduction in the water contact angle is less than 20%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photocurable hard coat resin composition and a hard coat film using the same. [Background technology]

[0002] In recent years, touch panels that combine display devices and input devices have been used in a wide range of fields. In particular, touch panels that use a touch pen as an input device allow for more intuitive operation by directly inputting characters and complex figures, and are being widely adopted in a wide range of applications, including tablet PCs, pen tablets, smartphones, and portable game devices.

[0003] Touch panels have a problem in that the screen is exposed and is directly touched by fingers, skin, pens, etc., and is therefore susceptible to dirt such as sebum and scratches. To address such problems, technologies have been developed to make the surface of the touch panel less susceptible to dirt, easier to clean, smooth, and less susceptible to scratches, and for example, a hard coat film has been proposed in which a hard coat layer containing a hydrolyzable silyl group or silanol group, a radical polymerizable compound, and a polymerization initiator and a surface layer are laminated in this order (Patent Document 1).

[0004] By using such hard coat film, it has become possible to prevent the occurrence of dirt adhesion and scratches considerably, but especially when using a touch pen, abrasion resistance that can maintain surface function for a long period of time is also required.However, there are not many hard coat films with sufficient abrasion resistance, and there are problems such as the water contact angle changing greatly and the antifouling property decreasing when the film surface is rubbed with something that rubs the film surface, such as an eraser, and there is room for improvement. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6519771 Summary of the Invention [Problem to be solved by the invention]

[0006] The object of the present invention is to provide a photocurable resin composition that has excellent optical properties as well as abrasion resistance and exhibits an extremely small rate of change in water contact angle even when rubbed with an eraser, and a hard coat (hereinafter referred to as HC) film having the resin cured layer. [Means for solving the problem]

[0007] In order to solve the above problem, the invention of claim 1 is as follows: On a plastic film substrate, A hard coat resin composition comprising a binder (A) containing a polythiophene compound, a fluorine-based silicone compound (B) having a reactive functional group, and a photopolymerization initiator (C), wherein the (A) contains a hexafunctional or higher (meth)acrylate, and the ratio of the (B) to 100 parts by weight of the photopolymerization component is 0.3 to 12.0 parts by weight, and the cured film has a water contact angle of 100° or more, and the decrease in the water contact angle after 1000 reciprocating strokes with an eraser under a load of 1 kg is less than 20%. and a total light transmittance of 90% or more. to provide.

[0008] The invention of claim 2 is the above (A) 2. The hard coat film according to claim 1, further comprising a cured layer of a hard coat resin composition, the content of the polythiophene compound being 0.8 to 5.0% by weight based on the total solid content. to provide.

[0009] The invention of claim 3 is as follows: 2. The hard coat coating according to claim 1, further comprising a cured layer of a hard coat resin composition, the cured film of which has a water contact angle of 110.1° or more. To provide a hard coat film.

[0010] The invention of claim 4 is as follows: 4. The method according to claim 1, wherein the haze is 1% or less. To provide a hard coat film. Effect of the Invention

[0011] The resin composition of the present invention has excellent optical properties and also has excellent abrasion resistance, with the rate of change in water contact angle being very small even when rubbed with an eraser, and is therefore useful as an HC resin for use in HC films for touch panels. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will now be described in detail.

[0013] The HC resin composition of the present invention comprises a binder (A) containing a polythiophene compound, a fluorine-based compound (B), and a photopolymerization initiator (C). In this specification, (meth)acrylate includes both acrylate and methacrylate.

[0014] The binder (A) containing a polythiophene-based compound used in the present invention is the main component constituting the hard coat film, and contains a conductive polythiophene-based compound. Polythiophene is a polymer of thiophene, a sulfur-containing heterocyclic compound, and is a compound that becomes conductive when electrons are added to or removed from the conjugated n orbital by doping. In particular, poly(3,4-ethylenedioxythiophene) (hereinafter PEDOT) is preferable in that it improves conductivity when combined with poly(4-styrenesulfonate) (hereinafter PSS), has high environmental stability, and has high light transmittance in a thin film. The inventors have found that water repellency can be stably maintained by combining this polythiophene-based compound with a specific binder.

[0015] The content of the polythiophene compound contained in (A) is preferably 0.3 to 5.0% by weight, more preferably 0.5 to 3.0% by weight, and particularly preferably 0.8 to 2.0% by weight, based on the total solid content. By making it 0.3% by weight or more, it is possible to sufficiently suppress the decrease in water contact angle after rubbing with an eraser, and by making it 5.0% by weight or less, it is possible to maintain a good appearance of the HC layer. The amount of blending can be determined based on the surface resistivity of the cured film, and specifically, it is preferably 1×10 8 ~1×10 12It is preferable that the conductivity is Ω / □. The reason why the decrease in the water contact angle can be suppressed by improving the conductivity is not clear, but it is speculated that the damage to the film can be reduced by making it difficult for static electricity to be generated when the eraser is rubbed, and as a result, the decrease in the water contact angle can be suppressed.

[0016] The binder (A) contains a 6- or higher functional (meth)acrylate that forms a network-like crosslinked structure in the cured product. The upper limit is preferably 15 or less functional, more preferably 12 or less functional. The binder to be used is not particularly limited as long as it is 6 or more functional, and examples of oligomers include urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, polycarbonate (meth)acrylate, acrylic (meth)acrylate, and diene (meth)acrylate, which can be used alone or in combination of two or more. Among these, urethane (meth)acrylate is preferred in terms of abrasion resistance and fast curing properties.

[0017] The urethane (meth)acrylate, which is the binder (A), may be, for example, a structure in which a polyfunctional (meth)acrylate having a hydroxyl group is reacted with a polyisocyanate. Examples of polyisocyanates include aliphatic polyisocyanates such as hexamethylene diisocyanate (hereinafter referred to as HDI), alicyclic polyisocyanates such as isophorone diisocyanate, and aromatic polyisocyanates such as diphenylmethane diisocyanate. Among these, HDI, which has excellent weather resistance and stretchability, is preferred. Examples of (meth)acrylates having a hydroxyl group include pentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and dipentaerythritol penta(meth)acrylate. Among these, pentaerythritol triacrylate is preferred.

[0018] The low molecular weight binder (A) is, for example, hexafunctional, and may be dipentaerythritol hexa(meth)acrylate (hereinafter referred to as DPHA). Binders with less than 6 functionalities, whether they are oligomers or low molecular weight monomers, are unsuitable because the water contact angle decreases greatly after rubbing with an eraser. The reason why the water contact angle decreases due to the decrease in the number of functional groups is not clear, but it is speculated that the decrease in curability makes the coating surface more susceptible to fine scratches, and the charging inside makes it easier for water to penetrate, resulting in a decrease in the contact angle.

[0019] In addition to the (A), the composition may contain a (meth)acrylate monomer having less than 6 functionalities in order to adjust the viscosity of the composition and improve adhesion to the substrate. For example, butyl (meth)acrylate, isobornyl (meth)acrylate, hydroxyethyl (meth)acrylate, (poly)ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, diglycerin tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, etc. may be mentioned, and these may be used alone or in combination of two or more kinds.

[0020] The fluorine-based compound (B) used in the present invention is a leveling agent that imparts antifouling (antifingerprint) and water repellency. Since it has a reactive functional group that undergoes a polymerization reaction with (A), it does not fall off over time from the cured film, and the effect can be sustained for a long time. From the viewpoint of reducing the frictional force with the eraser, it is preferable to use a fluorine-based silicone compound. In particular, when photocuring is performed under nitrogen purging (deoxidation) conditions, the effect can be enhanced. Commercially available fluorine-based silicone compounds include X-71-1203M (trade name: manufactured by Shin-Etsu Chemical Co., Ltd., solid content 20%), Megafac RS-851, RS-852 (trade names: both manufactured by DIC Corporation), and Opstar TU2225 (trade name: manufactured by JSR Corporation). Commercially available fluorine-based compounds include KY-1216 (trade name: manufactured by Shin-Etsu Chemical Co., Ltd., solid content 20%).

[0021] The amount of (B) to be blended relative to 100 parts by weight of the photocurable component is 0.3 to 12.0 parts by weight, preferably 0.35 to 11.0 parts by weight. If it is less than 0.3 parts by weight, the degree of decrease in the water contact angle when rubbed with an eraser becomes large, and if it exceeds 12.0 parts by weight, there is a tendency for a lot of cissing when made into a film, which deteriorates the appearance, and the haze tends to be high, so this is not acceptable.

[0022] The photopolymerization initiator (C) used in the present invention generates radicals when irradiated with ultraviolet light or an electron beam, and the radicals trigger the polymerization reaction, and general-purpose photopolymerization initiators such as benzyl ketal, acetophenone, and phosphine oxide photopolymerization initiators can be used. By arbitrarily selecting the light absorption wavelength of the polymerization initiator, it is possible to impart curability over a wide wavelength range from the ultraviolet region to the visible light region. Specifically, 2.2-dimethoxy-1.2-diphenylethan-1-one is a benzyl ketal, 1-hydroxy-cyclohexyl-phenyl-ketone and 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one are α-hydroxyacetophenones, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one is α-aminoacetophenones, and 2.4.6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2.4.6-trimethylbenzoyl)-phenylphosphine oxide are acylphosphine oxides, which may be used alone or in combination of two or more. Among these, it is preferable to use an α-hydroxyacetophenone that is less prone to yellowing, and examples of commercially available products include Irgacure 184 and 2959 (trade name: BASF Japan, α-hydroxyacetophenones).

[0023] The ratio of the (C) to 100 parts by weight of the photocurable resin component is preferably 0.5 to 10 parts by weight, more preferably 3 to 8 parts by weight. By adding 0.5 parts by weight or more, sufficient curability is achieved, and by adding 10 parts by weight or less, yellowing of the coating film and deterioration of storage stability can be prevented without excessive addition.

[0024] Furthermore, to the HC resin composition of the present invention, ultraviolet absorbers, antioxidants, colorants, defoamers, thickeners, anti-suspending agents, antistatic agents, anti-fogging agents, slip agents, antibacterial agents, antiviral agents, organic fine particles, inorganic fillers, and the like may be added as necessary.

[0025] The HC resin composition of the present invention is diluted with a solvent to a solid content of 10 to 70% in order to improve the coatability to organic plastic films. Examples of the solvent include alcohol-based solvents such as ethanol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, and diacetone alcohol, ketone-based solvents such as acetone, methyl ethyl ketone (hereinafter MEK), methyl isobutyl ketone, and cyclohexanone, ester-based solvents such as methyl acetate and butyl acetate, and ether-based solvents such as PGM, diethyl ether, and diisopropyl ether, which can be used alone or in combination of two or more kinds.

[0026] Examples of plastic film substrates onto which the HC resin of the present invention can be applied include polyester films, polyethylene films, polypropylene films, diacetyl cellulose films, triacetyl cellulose films, acetyl cellulose butyrate films, polyvinyl chloride films, polyvinylidene chloride films, polyvinyl alcohol films, ethylene vinyl alcohol films, polystyrene films, polycarbonate films, polymethylpentene films, polysulfone films, polyether ether ketone films, polyether sulfone films, polyether imide films, polyimide films, fluorine resin films, nylon films, acrylic films, cycloolefin (co)polymer films, and the like.

[0027] Among them, biaxially oriented polyester films are preferably used from the viewpoints of price, processability, dimensional stability, etc., and acrylic films and polycarbonate films are preferably used from the viewpoint of weather resistance. The thickness of the film may be about 23 μm to 250 μm.

[0028] The method for applying the HC resin composition of the present invention is not particularly limited, and can be any of known coating methods such as spray coating, roll coating, die coating, air knife coating, blade coating, spin coating, reverse coating, gravure coating, wire bar coating, etc., or gravure printing, screen printing, offset printing, inkjet printing, etc. The dry film thickness is preferably 0.5 μm to 20 μm.

[0029] After the HC resin composition of the present invention is applied, it is dried at 60 to 120° C. and cured using an ultraviolet ray irradiator. Examples of light sources for irradiating ultraviolet rays include low pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, carbon arc lamps, xenon lamps, metal halide lamps, electrodeless ultraviolet lamps, and LED lamps. The curing conditions are 500 mW / cm. 2 ~3000mW / cm 2 The irradiation intensity is 50 to 2,000 mJ / cm2 as the cumulative light quantity. 2 The irradiation atmosphere may be air, but is preferably an inert gas atmosphere such as nitrogen or argon.

[0030] The water contact angle of an HC film having a cured layer of the HC resin composition of the present invention is reduced by less than 20% after the film is reciprocated 1000 times with an eraser under a load of 1 kgf. If the reduction rate is less than 20%, it is considered that most of the antifouling component remains without being scraped off by the eraser test, and therefore the film can be judged to have excellent antifouling properties and excellent abrasion resistance.

[0031] The reason for using an eraser in the above is that the abrasion caused by an eraser is similar to that caused by a touch pen, and this evaluation allows for an approximate evaluation of the abrasion resistance to a touch pen. The abrasion resistance of optical films is generally evaluated using steel wool, but steel wool is literally a hard and thin metal wire, and the degree of abrasion caused by a touch pen is completely different, so the abrasion resistance caused by a touch pen cannot be evaluated using steel wool.

[0032] The eraser used in the above eraser test is a Korean MINOAN (product name: manufactured by MUNBANGSAWOO, diameter 6 mm), which is the eraser used in the abrasion resistance test, and is rubbed 1000 times back and forth under the conditions of a load of 1 kg, a rubbing speed of 40 rpm, and a stroke width of 50 mm using a flat friction tester manufactured by Toyo Seiki Seisakusho, and the water contact angle before and after is measured. In this specification, the water contact angle is a value measured based on the sessile drop method of JIS R 3257:1999.

[0033] The water contact angle before the eraser test is 100° or more, preferably 105° or more, and more preferably 110° or more. If it is 100° or less, it cannot be said that it has sufficient antifouling properties, and it is difficult to suppress the adhesion of fingerprints and dirt. The water contact angle after the eraser test is reduced by less than 20% from the measured value before the test, preferably less than 10%, and more preferably less than 6%. If it is 20% or more, it cannot be said that it has sufficient abrasion resistance, and the antifouling properties decrease significantly over time when rubbed with a touch pen.

[0034] The present invention will be described in detail below based on examples and comparative examples, but these are specific examples and are not intended to be limiting. Unless otherwise stated, measurements were performed at room temperature of 25°C and relative humidity of 65%. The amounts of ingredients are expressed in parts by weight, and are expressed in terms of solid content except for the dilution solvent.

[0035] Example 1 Example 1, an HC resin composition, was prepared by mixing Z-885B-AS (product name: manufactured by Aica Kogyo Co., Ltd., polythiophene-based compound: PEDOT / PSS at 1% of total solids, binder: hexafunctional urethane acrylate obtained by reacting HDI and PETA) as (A), X-71-1203M (product name: manufactured by Shin-Etsu Chemical Co., Ltd., solids content 20%) as (B), and Omnirad184 (product name: manufactured by Shin-Etsu Chemical Co., Ltd., α-hydroxyacetophenone-based) as (C) with butyl acetate, MEK, PGM, and diacetone alcohol as dilution solvents in the formulation shown in Table 1 until uniformly dissolved and dispersed, according to the mixture shown in Table 1.

[0036] Examples 2 to 6 In addition to the materials used in Example 1, Z-702 was used as (A). B Using KY-1216 (product name: manufactured by Shin-Etsu Chemical Co., Ltd., solid content 20%) as (B), and stirring until uniformly dissolved and dispersed in the formulation described in 1, HC resin compositions of Examples 2 to 6 were prepared.

[0037] Comparative Examples 1 to 5 In addition to the materials used in the examples, Z-879A-AS (trade name: manufactured by Aica Kogyo Co., Ltd., polythiophene-based compound: PEDOT / PSS was 1% of the total solid content, binder: 5-functional urethane acrylate obtained by reacting HDI fluoride with PETA and 2-hydroxyethyl acrylate) and Z-850A-AS (trade name: manufactured by Aica Kogyo Co., Ltd., polythiophene-based compound: PEDOT / PSS was 1.4% of the total solid content, binder: ditrimethylolpropane triacrylate, 4-functional) and DPHA and Urea A (6-functional urethane acrylate obtained by reacting HDI and PETA) were mixed as binders and stirred until uniformly dissolved and dispersed in the formulation shown in Table 2 to prepare comparative examples 1 to 5, which are HC resin compositions.

[0038] Adjustment of HC film The coating was applied to an A4-sized polyethylene terephthalate film U403 (product name: Toray Industries, 100 μm, with easy-adhesion layers on both sides) so that the film thickness when cured would be 2 μm, and after drying at 80°C for 1 minute in a thermostatic chamber, the film was purged with nitrogen and cured with ultraviolet light using an electrodeless UV irradiation device F300S / LC-6B manufactured by Fusion UV Systems Japan, with an output of 1200 mW / cm2 using an H bulb and an accumulated light quantity of 200 mJ / cm2.

[0039] Table 1 JPEG0007630263000001.jpg80135

[0040] Table 2 JPEG0007630263000002.jpg110135

[0041] The evaluation method was as follows.

[0042] Appearance: The coated surface of the HC film prepared above was visually inspected. If there were no defects such as bumps, repelling, or uneven coating, and the surface was in good condition, it was marked with an O. If there were defects, it was marked with an X.

[0043] Total light transmittance: Measured in accordance with JIS K7361-1 using Haze-GARD2 manufactured by Toyo Seiki Seisakusho, with 90% or more being rated as ◯ and less than 90% being rated as ×.

[0044] Haze: Measured in accordance with JIS K7361-1 using Haze-GARD2 manufactured by Toyo Seiki Seisakusho, with 1% or less being rated as ◯ and over 1% being rated as ×.

[0045] Surface resistivity: The coated surface of the HC film prepared above was measured in accordance with JIS K6911 using a high resistivity meter HIRESTA-UX manufactured by Nitto Seiko Analytech Co., Ltd., and found to be 1.00 x 10 12 Cases exceeding Ω / □ were marked as ×.

[0046] Water contact angle: MINOAN (trade name: MUNBANGSAWOO, diameter 6 mm) was used, and a flat friction tester manufactured by Toyo Seiki Seisakusho was used to rub 1000 times back and forth under the conditions of a load of 1 kg, a rubbing speed of 40 rpm, and a stroke width of 50 mm, and the water contact angle was measured before and after. The water contact angle was measured according to the static drop method of JIS R 3257:1999, using DMs-400 manufactured by Kyowa Interface Science Co., Ltd., after dropping water at room temperature and leaving it for 30 seconds. The evaluation was performed by taking the difference between the initial water contact angle and the water contact rate after abrasion with an eraser as the water contact angle change rate, with less than 10% being ◎, 10 to less than 20% being ◯, and 20% or more being ×.

[0047] Evaluation result 1 JPEG0007630263000003.jpg73135

[0048] Evaluation result 2 JPEG0007630263000004.jpg85135

[0049] The examples were satisfactory with no problems in terms of appearance, total light transmittance, haze and water contact angle.

[0050] On the other hand, Comparative Example 1 in which the amount of (B) was less than the lower limit, Comparative Examples 2 and 3 in which the number of functional groups of (A) was less than 6, and Comparative Examples 4 and 5 in which the binder did not contain a polythiophene-based compound all had large rates of change in water contact angle, and all of these were unsuitable for the present invention.

Claims

1. On a plastic film substrate, The composition includes a binder (A) containing a polythiophene-based compound, a fluorine-based silicone compound (B) having a reactive functional group, and a photopolymerization initiator (C), The (A) contains a hexa- or higher functional (meth)acrylate, The ratio of the (B) to 100 parts by weight of the photopolymerization component is 0.3 to 12.0 parts by weight, a cured layer of a hard coat resin composition, the cured film having a water contact angle of 100° or more, and a decrease in the water contact angle of less than 20% after 1000 reciprocating strokes with an eraser under a load of 1 kg; A hard coat film having a total light transmittance of 90% or more.

2. 2. The hard coat film according to claim 1, comprising a cured layer of a hard coat resin composition, the content of the polythiophene compound contained in (A) being 0.8 to 5.0% by weight based on the total solid content.

3. The hard coat film according to claim 1, characterized in that it has a cured layer of a hard coat resin composition, the cured film having a water contact angle of 110.1° or more.

4. A hard coat film described in any one of claims 1 to 3, characterized in that the haze is 1% or less.

Citation Information

Patent Citations

  • Conductive polymer dispersion liquid and method for producing the same, and method for producing conductive film

    JP2019131768A

  • Hard coat film and window and image display device containing the same

    JP2021056514A

  • Hard coat film and window and image display device containing the same

    JP2021056515A

  • Hard coated film and information display device

    JP6519771B2

  • Ultra violet curing hard coating composition having anti-smudge and anti-static properties

    KR1020120115883A